Face Recognition Using Eigen Face Based Technique Utilizing the Concept of Principal Component Analysis - Bandyopadhyay, Prof. Samir K; Roy, Mrs. Sunita (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Face recognition has been an active research area since late 1980s [1]. Eigenface approach is one of the earliest appearance-based face recognition methods, which was developed by M. Turk and A. Pentland [1] in 1991. In this approach we have to perform a lots of computations, which are not feasible with respect to time in many real time system. The concept of principal component analysis (PCA) is used in this approach to reduce the dimension and hence reducing the computation time. Principal component analysis [4] decomposes face images into a small set of characteristic feature images called eigen faces.